Dengue prevention practices among community in dengue hotspot area - Said, Muhammad Faridzuan Faiz; Abdullah, Hasmah; Abdul Ghafar, Noraini (International Journal Of Community Medicine And Public Health, 2018)
Background: Dengue is one of the most important mosquito-borne diseases which can cause a major problem to human health. Poor practices in dengue prevention especially in the area where dengue is prevalent is among the factors contributing towards dengue spike. This study was commenced to assess the level of attitude and practice toward dengue prevention among the community residing in a dengue prone area, beside identifying the environmental characteristics surrounding the housing compound. Methods: A cross-sectional study was conducted among 132 respondents living in a dengue hot spot area. A set of questionnaire form consisted of four parts; socio-demographic information, environmental characteristics around the house, and attitudes and practices toward dengue prevention were distributed to respondents. Results: More than half of the respondents possessed good level of attitude, and more than half scored moderately for practice (57.6% and 56.1% respectively). Data on the environmental characteristics showed that majority of the respondents’ houses have no potential breeding sites for Aedes mosquito. Findings also indicate that there was no significant association between dengue prevention practices and socio-demographic factors such as age, gender, educational level and occupational status. Conclusions: Level of practice of dengue prevention is still considerably low and could be improved through educational campaign. Proper knowledge and information regarding dengue practices should be emphasized among the community especially in high risk area to raise up the awareness and cultivate better practices for dengue prevention.